Insider trading, costly monitoring, and managerial incentives - Jie Hu; Thomas H. Noe (Federal Reserve Bank of Atlanta, 1997)
In this paper we show, in an incomplete contracts framework that combines asymmetric information and moral hazard, that by permitting insiders to trade on personal account the equilibrium level of output can be increased and shareholder welfare can be improved. There are two reasons for this. First, insider trading impounds information regarding the costs and benefits of effort and perk consumption into asset prices, which allows shareholders to choose more efficient portfolio allocations. Second, allowing insider trading can induce managers to increase their stake in the firm beyond that obtained through bargaining with shareholders. This effect leads to a reduction in managerial perk consumption and/or increased managerial effort. Insider trading can also be costly for shareholders' intermediate range of monitoring costs and project difficulty because, in such cases, the efforts of managers are quite sensitive to the exact level of fractional shareownership, which managers can endogenously change if they are able to trade on personal account. Interestingly, when monitoring and effort costs are low, managers may prefer restrictions on their ability to trade as such restrictions will force shareholders to offer them a larger fraction of output.
Keywords: 330; Financial markets; Stock market